KAJIAN ATAS PENERAPAN AKUNTANSI PERPAJAKAN PADA UMKM CV. X - Ismail Zulhaj Tuasikal; Azkia Buana; Tazakka Imammareto; Daffa Raihan Mahesa; Tias Suningsih; Satria Wahyu Hidayat (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This study aims to analyze the implementation of Tax Accounting in MSME CV X based on the provisions set by the government. The study uses a qualitative method with a library research approach and descriptive analysis of secondary data obtained from journals, tax regulations, and CV X's financial data. The results of the study indicate that CV X is one of the MSMEs that comply with tax obligations through the e-Billing and Coretax systems. With an annual turnover of Rp 1,596,477,200, CV X is subject to a Final Income Tax rate of 0.5% in accordance with the provisions stipulated by the Directorate General of Taxes. The implementation of this policy has been proven to facilitate business actors in calculating and reporting taxes, while simultaneously encouraging the level of tax compliance without burdening operational activities. However, challenges are still found in the aspects of technical understanding and adaptation to the digital tax system. This study concludes that PP No. 23 of 2018 is effective in simplifying the MSME tax system and supporting the growth and compliance of taxpayers in Indonesia.